Comprehend different ways of teaching commercial terms through reading skills - Toshpulatov Dilshodjon Abdurafikovich (Utilitas Mathematica, 2025)
In this article, I have suggested some useful ways of teaching commercial terms through reading skills. I hope that the methods and ideas that I offer to eliminate the problems encountered in teaching will help the person who reads this article to get useful and valuable information about how to effectively read commercial texts without any misunderstanding. This article discusses the importance of skimming and scanning unfamiliar questions encountered in reading in order to avoid translation problems as much as possible.